A Novel Form of AEBP2-Containing PRC2.2 Is a Genetic Dependency in Germinal Centre B-Cell Lymphoma and Its Targeting Can Overcome Acquired Resistance to EZH2 Inhibition - Bracken, Adrian (My University, 2024)
EZH2 is the catalytic subunit of Polycomb Repressive Complex 2 (PRC2) and plays a central role in B-cell lymphopoiesis. EZH2 is an oncogene in B-cell lymphoma with recurrent change-of-function hotspot mutations causing decreased levels of di-methylation of H3K27 (H3K27me2), coupled with increased levels of H3K27me3. Although enzymatic inhibitors of EZH2 are entering the clinic for the treatment of selected patients with B-cell lymphoma, their utility is limited by disease progression due to acquired resistance. Overcoming acquired resistance to EZH2 inhibitors will assist in their application in the clinic and improve patient outcomes.
PUBLISHED
Keywords: PRC2